Antecedents and consequences of satisfaction with work–family balance: A moderating role of perceived insider status. (22nd June 2017) - Choi, Jaepil; Kim, Andrea; Han, Kyongji; Ryu, Seongmin; Park, Jong Gyu; Kwon, Bora
Summary: This study developed a moderated mediation model to investigate how family‐supportive paid leave and supervision affect employees' satisfaction with work–family balance and in turn their affective organizational commitment and supervisor‐directed organizational citizenship behavior depending on their perceived insider status in the organization. Our analysis of data collected from 118 employee–supervisor dyads in Korean organizations revealed that satisfaction with work–family balance mediated the linkages from family‐supportive supervision to affective organizational commitment and supervisor‐directed organizational citizenship behavior, and the linkage from family‐supportive paid leave to affective organizational commitment. Results further showed that the entire mediational process for family‐supportive supervision was more pronounced for those who perceived themselves to be an insider of their organizations, while the same pattern was not found for the meditational process related to family‐supportive paid leave. Our findings provide theoretical implications for work–family balance research and offer practical suggestions to make employees satisfied with work–family balance.